KOMUNIKASI MASSA DALAM SIARAN RADIO - Ayu Wilantari (Dharma Duta, 2019)
Storytelling or storytelling has become an oral culture in Indonesian society this oral culture or tradition is a hereditary heritage. The times are getting more advanced and radio is present as a mass media that facilitates the oral culture. Radio is a means of mass media communication or often referred to as mass communication. Radio in broadcasting has broadcasters as the most important position in the success of a program that they make. Fast and direct, familiar with the listener, warm, simple, unlimited, inexpensive, able to repeat and flexible entertainment facilities which are the advantages of radio, while fleeting, global, time-limited, linear, contain disturbances in broadcasting and are local to radio shortages..